AKTUALISASI NILAI-NILAI TAUHID SURAT AL-FATIHAH PADA PENDIDIKAN ISLAM (Telaah atas Tafsir Al-Qosimi dan Tafsir Fathul Qodir) - EFENDI, NAWAWI (2011)
Oneness of God (Tawheed) is essence of worship in Islam. It is also spirit that gives noble values to all aspects of life, including islamic education. The spirit of tawheed will guide islamic education in order to be on ashalatud diin (the basic values of Islam religion) so that islamic education will not be influenced by negative current of globalization in this digital era. But, if Muslims want to know tawheed values -in the Koran or in hadeeth -they must refer to interpretation (tafseer) of Muslim scholars (ulama) that have competence in tafseer so that they do not fall on wrong interpretation that lead them astray. Purposes of the research are to know tawheed values in surah Al-Fatihah and to actualize it to islamic education. Such a matter needs to be emphasized in order islamic education is not 'dry' of tawheed values so that all people who have responsibility in education will make the effort of islamic education as worship to Allah. Tawheed values also will save islamic education from liberalization project of islamic education that is recently propagandized. Method of research that the writer used in this research is qualitative and comparative study by research library method. The steps that are used are comparing among Al-Qosimi interpretation and Al-Syaukani interpretation on surah Al-Fatihah, then finding tawheed values from both interpretations. Furthermore, the values is reflected and actualized in islamic education in general. Results of this research indicated that surah Al-Fatihah is full of tawheed values that can indeed be spirit of islamic education. One of the form of it's actualization is that islamic education must be able to create it's own curriculum, namely the curriculum that is based on tawheed values. With such an islamic curriculum, islamic education will not separate Islam from knowledge or separate knowledge from Islam.